SCIENCE AND INTELLECTUAL LIFE IN THE QASHQADARYO OASIS FROM THE 16TH TO THE EARLY 20TH CENTURY - Utkir Rajabaliyev (Western European Studies, 2025)
This article provides an in-depth analysis of the development of scientific thought and intellectual culture in the Qashqadaryo oasis between the 16th and early 20th centuries. It explores the role of madrasahs, prominent scholars, manuscript culture, and the impact of political and social changes on scientific activities. By tracing the interplay of traditional Islamic scholarship and emerging modern influences, this study reveals the resilience and evolution of knowledge in one of Central Asia’s historically rich regions
Keywords: Qashqadaryo oasis; Central Asia; Islamic scholarship